2021
DOI: 10.1172/jci.insight.149228
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive waves of innate immune response in the retina in experimental autoimmune encephalomyelitis

Abstract: Figure 7. CSLO image processing for the morphological analysis of innate immune cells. The image preparation on ImageJ includes background subtraction (-50 px), contrast enhancement (saturated pixels 1%), and Z-stacking after image alignment. Then, a sample area of 350 px (red circle) in the vicinity of the optic nerve head is selected, and the number of cells are measured (somata areas are not shown).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…These data indicated that the retinae of both mouse strains participated in the inflammatory response despite the lack of inflammatory infiltrates from the systemic compartment. This observation was consistent with the idea of waves of resident innate immune cell activation in the retina during EAE that has been previously reported [ 14 ]. Notably, a decrease of neurotrophic factors (BDNF and CNTF) was apparent in the retina in the course of EAE, and the expression of both neurotrophic factors was below baseline in the recovery phase – again with similar dynamics in wild-type and Aqp4 –/– retinae (Supplementary Fig.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These data indicated that the retinae of both mouse strains participated in the inflammatory response despite the lack of inflammatory infiltrates from the systemic compartment. This observation was consistent with the idea of waves of resident innate immune cell activation in the retina during EAE that has been previously reported [ 14 ]. Notably, a decrease of neurotrophic factors (BDNF and CNTF) was apparent in the retina in the course of EAE, and the expression of both neurotrophic factors was below baseline in the recovery phase – again with similar dynamics in wild-type and Aqp4 –/– retinae (Supplementary Fig.…”
Section: Resultssupporting
confidence: 93%
“…However, the retinal thickness correlates with the inflammatory response in the CNS of EAE mice as well [ 9 ]. Since we did not detect inflammatory infiltrates in the retinae of either wild-type or Aqp4 –/– mice, it is possible that remote effects of the inflammatory process in the optic nerve or activation of resident innate immune cells [ 14 ] might trigger retinal swelling. The increase in retinal TNF RNA levels during EAE, which has also been shown previously [ 9 ], and the detection of Iba1 + cells are consistent with this concept and might correspond to the first wave of innate immune activation in the retina during EAE [ 14 ] – well before retrograde axonal degeneration occurs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been associated with blood-brain barrier permeability, dysregulated T-cell activation and modulating effects on B-cells (13)(14)(15)(16)(17)(18)(19). Using non-invasive, in vivo confocal scanning laser ophthalmoscopy (cSLO), microglial activation can also be assessed in the retina of CX3CR1 GFP mice in the context of EAE (20).…”
Section: Introductionmentioning
confidence: 99%
“… 16 Moreover, recent in vivo data from myelin oligodendrocyte glycoprotein 35-55 experimental autoimmune encephalomyelitis showed a strong and dynamic microglial activation following optic neuritis (ON). 17 …”
mentioning
confidence: 99%